Determinants and Measurement Quality of the Financial Statements of Local Governments in Indonesia - Nur, Basyiruddin; Sembel, Roy; ., Khomsiyah; Gunawan, Juniati (Journal of Accounting, Business and Finance Research, 2021)
The aim of this research is to create a measurement index of the quality of the financial statements of local governments (FSLGs) using data from the accountability and performance reports on government entities (APRGEs), FSLG notes, and the internal control systems (ICS). The APRGEs have many indicators, but the relevant ones are the accounting information system (AIS), competence, performance, and good government governance (GGG). The measurement index sourced from the APRGEs is calculated from the percentage of performance achieved for every indicator. There are 35 main and seven conditional indicators taken from the FSLG notes. The ICS has 101 indicators. The sample comprises 25 local governments of provinces, cities and municipalities from 2015 to 2018. EViews 8 was used for statistical computation. The output of the measurement index is the FSLG quality assessment category. The index can be used to measure the quality of FSLGs produced by local governments. The results of the statistical testing show that competence and GGG affect the quality of FSLGs, but AIS and performance do not. However, AIS and performance can still be used to measure the quality of FSLGs. AIS is a primary need that cannot be left out of the process of presenting FSLGs. Likewise for performance, each local government already has its own key performance indicators (KPIs) which will enable the civil state apparatus (CSA) to operate efficiently and follow the rules, including the preparation of FSLGs. The implication is to facilitate internal and external parties in assessing and improving the quality of financial statements of local governments.